(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to examine the effect of the length to diameter ratio of the floating stone column on settlement behavior. The load vs settlement labouratory tests are performed with the length to diameter ratio of floating stone column as 0, 2, 4, 5, and 6 of the stone column to find the corresponding settlement behavior. This research finding shows that the load-carrying capacity of the floating stone column increases with the increasing length to diameter ratio of the floating stone column up to a certain limit. Beyond that limit the load-carrying –capacity is not increased even by increasing the length of the stone column. This research is very helpful in the geotechnical engineering field where ground improvement work is required in the form of a stone column.